Notary Responsibility For Lost Authentic Deeds - Salsabila, Sabila (Universitas Islam Malang, 2024)
Abstract : Notary as public officials has to obey and submit to applicable regulations, adhere to the Law on the position of Notaries and also adhere to the Notary's ethics code. If a Deed which is made by the Notary gives rise to a dispute or lawsuit, so this deed needs to be questioned. This research focuses on studying legal protection for notaries in making deeds related to the fake documents by related parties. This research uses normative legal research by examining library materials. The result of this research is making a deed by a notary that carry out systematically according to the positive law of making a deed by paying attention to the structural stages of the procedure for making a deed. The principle of caution in making a deed must be possessed by every notary in order to create an authentic deed which is legally strong. Notaries in carrying out their duties have the right to recusal, the right to leave, and the right to receive an honorarium for their legal services. Deeds is made based on forged documents can become null and void after going through a series of court procedures. Notaries as passive parties in making deeds using fake documents cannot be caught in the law.Keywords: Notary, Deed, Fake Document